2021
DOI: 10.9734/jsrr/2021/v27i130350
|View full text |Cite
|
Sign up to set email alerts
|

Re-Isolation Methodologies for Recovering Sporulation of Eucalyptus Pestalotiopsis grandis-urophylla Isolates after 14 Months Storage

Abstract: After long periods of storage, plant pathogen isolates lose their sporulation capacity. The objective of this study was to evaluate re-isolation methodologies for recovering sporulation of Pestalotiopsis grandis-urophylla isolates after subjection to a long period of storage. Isolates of P. grandis-urophylla were kept for 14 months on Petri dishes with PDA medium at 10°C. After this period, the isolate colonies showed reduced mycelial growth and no sporulation. The isolates were inoculated on healthy Eucalyptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Finally, the results about the AUDPC were similar with the results obtained by Silva et al (2021), on what the isolates E-72-02, E-72-03 and E-72-04 shown results of AUDPC vary from 128 to 188. Such data concordance sugest that the final size of lesions was indifferent to the inoculation method, since Silva et al (2021) used agar plugs containing fungal mycelium which was depositet on leaf surface.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Finally, the results about the AUDPC were similar with the results obtained by Silva et al (2021), on what the isolates E-72-02, E-72-03 and E-72-04 shown results of AUDPC vary from 128 to 188. Such data concordance sugest that the final size of lesions was indifferent to the inoculation method, since Silva et al (2021) used agar plugs containing fungal mycelium which was depositet on leaf surface.…”
Section: Resultssupporting
confidence: 86%
“…In a similar study, mycelial growth was shown to be a useful variable in separating isolates of Pestalotiopsis (Lazarotto et al, 2014). The reaction of phytopathogens isolates to different physical factors, such as in vitro culture or any other factor that can influence the pathogenicity power, are the main tools that subsidies studies related to epidemiology of diseases under field conditions (Silva et al, 2021). Thus, we believe that studies directed to the pathogenic behavior of different species and isolates of Pestalotiopsis should be conducted in order to help the understanding of its pathogenic strength and also the behavior of its pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation